Enhancing departmental preparedness for COVID-19 using rapid-cycle in-situ simulation. Issue 4 (August 2020) - Dharamsi, A.; Hayman, K.; Yi, S.; Chow, R.; Yee, C.; Gaylord, E.; Tawadrous, D.; Chartier, L.B.; Landes, M.
Summary: In response to coronavirus disease 2019 (COVID-19), a rapid-cycle in-situ simulation (ISS) programme was developed to facilitate identification and resolution of systems-based latent safety threats. The simulation involved a possible COVID-19 case in respiratory failure, using a mannequin modified to aerosolize phosphorescent secretions. Thirty-six individuals participated in five ISS sessions over 6 weeks, and a further 20 individuals observed these sessions. Debriefing identified latent safety threats from four domains: personnel, personal protective equipment, supply/environment and communication. These threats were addressed and resolved in later iterations. Ninety-four percent of participants felt more prepared to care for a potential case of COVID-19 after the ISS.